Long-term safety evaluation of mirtazapine: A real-world pharmacovigilance study based on the FAERS database - Kaidi Zhao; Jiashu Liu (PLoS ONE, 2026)
Background Mirtazapine is widely used in the treatment of major depressive disorder (MDD), yet its real-world safety profile remains insufficiently evaluated. Methods This study analyzed adverse event (AE, plural AEs) reports related to mirtazapine from the FDA Adverse Event Reporting System (FAERS) database between the first quarter of 2004 and the first quarter of 2025. Four disproportionality analysis methods were employed, including reporting odds ratio (ROR), proportional reporting ratio (PRR), Bayesian confidence propagation neural network (BCPNN), and multi-item gamma Poisson shrinker (MGPS). Additional analyses included sensitivity analysis, time-to-onset (TTO) evaluation, and Weibull distribution modeling. Results A total of 17,953 reports were included, with females accounting for 54.1% and males for 37.7%. In 48.4% of the reports, patients were aged between 18 and 65 years. Overall, 65.0% of the reports were submitted by healthcare professionals. Known AEs such as somnolence (n = 887, ROR = 4.57, PRR = 4.52, EBGM = 4.50, IC = 2.17), QT interval prolongation (n = 259, ROR = 7.35, PRR = 7.32, EBGM = 7.27, IC = 2.86), suicidal ideation (n = 601, ROR = 6.65, PRR = 6.59, EBGM = 6.55, IC = 2.71), and rhabdomyolysis (n = 146, ROR = 3.66, PRR = 3.65, EBGM = 3.64, IC = 1.87) showed positive signals. In addition, several unexpected AEs also exhibited positive signals, including restless legs syndrome (n = 305, ROR = 17.05, PRR = 16.97, EBGM = 16.65, IC = 4.06), neuroleptic malignant syndrome (n = 158, ROR = 13.77, PRR = 13.74, EBGM = 13.53, IC = 3.76), and nightmare (n = 279, ROR = 8.02, PRR = 7.99, EBGM = 7.93, IC = 2.99). TTO analysis showed that 59.52% of AEs occurred within the first month of treatment. The results of the sensitivity analyses further supported the robustness of these findings. Conclusion This study systematically assessed the long-term safety profile of mirtazapine using 21 years of real-world pharmacovigilance data from the FAERS database. The findings provide important evidence to support safe clinical use of mirtazapine and emphasize the need for continuous safety monitoring.